2013
DOI: 10.1186/1897-4287-11-19
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genetic variants in inflammatory-related genes on prostate cancer risk among men of African Descent: a case control study

Abstract: PurposeAlthough case–control studies have evaluated the role of variant inflammatory-related loci in prostate cancer, their impact is virtually unknown among men of African descent. To address this, we evaluated the impact of inflammatory cytokine single nucleotide polymorphisms (SNPs) on prostate cancer risk for men of African descent.MethodsForty-four SNPs in inflammatory cytokine-associated genes were evaluated among 814 African-American and Jamaican men (279 prostate cancer cases and 535 controls) using Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
2
18
1
Order By: Relevance
“…Kohaar et al (2007) demonstrated that a single-nucleotide polymorphism (SNP) at -308 (G/A) of the TNFα promoter increased the risk of HPV infection and development in cervical cancer in Indian women. Although many studies have been performed to investigate the associations between the TNF-α 308G/A polymorphism and urogenital cancers, the results of these studies are controversial (Wu, 2004;Nonomura et al, 2006;Danforth et al, 2008;Wang et al, 2011;Barbisan et al, 2012;Jones et al, 2013). In Wu et al study (2004), 126 healthy people and 96 patients with prostate cancer were examined and their results suggested that prostate cancer appears to be associated with the p53 gene codon 72 polymorphisms, but not with the TNF-α gene.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kohaar et al (2007) demonstrated that a single-nucleotide polymorphism (SNP) at -308 (G/A) of the TNFα promoter increased the risk of HPV infection and development in cervical cancer in Indian women. Although many studies have been performed to investigate the associations between the TNF-α 308G/A polymorphism and urogenital cancers, the results of these studies are controversial (Wu, 2004;Nonomura et al, 2006;Danforth et al, 2008;Wang et al, 2011;Barbisan et al, 2012;Jones et al, 2013). In Wu et al study (2004), 126 healthy people and 96 patients with prostate cancer were examined and their results suggested that prostate cancer appears to be associated with the p53 gene codon 72 polymorphisms, but not with the TNF-α gene.…”
Section: Discussionmentioning
confidence: 99%
“…The TNF-α 308G/A polymorphism is a G/A polymorphism at nucleotide (nt) -308, and is associated with the development of several urogenital cancers, including prostate cancer (Zabaleta et al, 2008;Moore et al, 2009;Jones et al, 2013), cervical cancer (Singh, 2009;Zuo et al, 2011), bladder cancer (Jeong et al, 2004;Kim et al, 2005;Leibovici et al, 2005), and renal cell carcinoma (Jang et al, 2001). For example, Jeong et al (2004) studied 113 patients with bladder cancer and 109 healthy subjects and found that the genotype of the 308 nucleotide in the TNF-α promoter had a statistically significant effect on TNF-α production and was related to the bladder tumor grade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the inflammatory factors, cytokines (interleukins and TNFs) and chemokines (CC, CXC, XCL, and C-X3-C), are known to play an important role in host response to infection, inflammatory process, tumor development and metastasis [Jones, et al 2013]. Studies suggest that single nucleotide polymorphisms (SNPs) in inflammatory related genes and altered expression play a role in development and survival of various cancers including PC [Chang, et al 2009].…”
Section: Introductionmentioning
confidence: 99%